Evidence-Based Practice: Community-Based Palliative Cancer Care - Jajang Ganjar Waluya; Nur Maziyya; Eva Nurlaela; Ita Vusfita; Ihda Al Adawiyah Mz; Kusman Ibrahim; Ikeu Nurhidayah; Laili Rahayuwati (Journal of Nursing Care, 2019)
Prevalence of  cancer is estimated will increase in the next two decades. Therefore, there is a challenge for health provider to encounter treatment and caring for the patients. Especially, the cancer patients face several problems not only physical but also psychological, emotional, spiritual and social cultural aspects.This study explored the evidence-based practice on community-based palliative cancer care. Literature study is done by making a summary of published articles related to the question. The searching method used several electronic databases such as Google Scholar, Proquest, and PubMed. Articles under the keywords of “Palliative Cancer Care”, “Community”, and “Nursing” reach as much as 1.804. The inclusion criteria for this literature review were articles that have been peer-reviewed, are in full-text, in either English or Indonesian, and publication year from 2008 to 2018. Meanwhile, the exclusion criteria include those that do not follow a standardized structure of an article (consisting of Abstract, Introduction, Method, Result, Discussion, Implication, and Reference), are in the form of a review, and whose content does not answer research questions.Results: The United States of America is on the highest place regarding palliative care service, following by community-based palliative cancer implementation in Europe. Asian countries had been applying palliative care service, integrated with national health care system. In the Middle East countries, palliative care program ranks the lowest, but in implementation, they have discreetly performed community-based palliative care. In Africa, it is not the main focus in the field of health. Palliative care for cancer patients that is potential for development in Indonesia is that of family-based.Conclusion: Community-based palliative care is a variant of palliative treatment long applied and being developed in many countries in the world. In continents such as America and Europe, the implementation of palliative care ranks the highest place. In Indonesia, it is done partially and only available in hospitals or non-governmental organization. In the level of community, family-based palliative care can be developed by involving trained family members.